Effects of land cover, topography, and soil on stream water quality at multiple spatial and seasonal scales in a German lowland catchment - Chaogui Lei (Elsevier, 2021)
The influence of catchment characteristics on water quality varies with space and time. Understanding the key factors influencing water quality is needed for effective land use and riparian management to protect river health. To this end, we quantified effects on stream water quality in summer and winter between 1992 and 2019 at multiple spatial scales in the upper Stör catchment, Germany. We applied multivariate statistical analyses on three scales: the catchment, riparian, and reach scale. Our results indicated that poorer water quality mostly occurred in winter and in steeper arable and pasture areas and in wetlands. Water quality was strongly affected by soil properties, land use composition (the areal shares of arable or pasture land respectively with slopes >2%, forest, and urban) and configuration. The spatial variation of the overall water quality was better explained at the larger scales (riparian and catchment) and in summer (73–78%). The most important variables differed among scales and for the different water quality variables. Forest and complex landscape patterns showed more negative correlations with degraded water quality at the reach scale when compared to larger scales. At larger scales, besides permeable and organic soils, steeper arable lands were most significant for nitrate-nitrogen (NO3-N) and steeper pasture areas for phosphate-phosphorus (PO4-P) pollution. The results of this study provide valuable insights for guiding sustainable and spatially specific land-water management of river catchments at different scales to improve stream water quality.